SOCIAL DEIXIS IN THE DIGITAL COMIC OF LORE OLYMPUS WEBTOON - Shelby Rihadatul Huwaidah; Yuli Widiana (Humaniora Scientia, 2023)
Social deixis is one of the pragmatics studies. The study of social deixis is also found in digital comics. Therefore, this research discusses the use of social deixis to identify the types of social deixis and their functions in the Lore Olympus Webtoon. This research is classified as qualitative descriptive research. All of the data of this research were taken from the conversations in the webtoon entitled Lore Olympus which contain social deixis. The result of this research shows that there are two main classifications of social deixis used in the Lore Olympus Webtoon namely relational social deixis and absolute social deixis. Relational social deixis includes four sub-classification types, 1) speaker and referent; 2) speaker and addressee; 3) speaker and bystander; 4) speaker and setting. Then, absolute social deixis consists of 1) authorized speaker; and 2) authorized recipient. Furthermore, the result of this study shows that there are three functions of social deixis namely to express politeness and respect, to express intimacy, and to identify authority. In general, understanding social deixis means learning more to show respect, and politeness between the speakers and the addressee by mentioning the specific title or call based on the context